2013
DOI: 10.1097/rli.0b013e31829a4f2f
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Thoracic Blood Flow Using Volumetric Magnetic Resonance Imaging With Radial Velocity Encoding

Abstract: Objectives To validate radially undersampled 5-point velocity-encoded time-resolved flow-sensitive MRI (“PC-VIPR”) for quantification of ascending aortic (AAO) and main pulmonary artery (MPA) flow in-vivo Materials and Methods Data from 18 healthy volunteers (41.6±16.2years (22–73); BMI 26.0±3.5 (19.1–31.4) scanned at 3T with a 32-channel-coil were included. Left and right ventricular stroke volumes (LVSV and RVSV, respectively) calculated from contiguous short-axis CINE-bSSFP slices were used as the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
(40 reference statements)
3
32
0
Order By: Relevance
“…As previously reported (Table 4), we found that flow volume [1416, 21, 25, 26] and peak flow [14] were lower and that peak velocities were higher [18] when estimated using 4D flow in comparison with 2D measurements. Of note, our net volume measurements were lower than those previously reported both at 3T (2D-1dir = 89 ± 10 ml [18] or 100.6 ± 27.8 ml [16] and 4D flow = 88 ± 10 ml [18] or 95.9 ± 19.1 ml [16] in the AA). This could be due to the differences in the studied populations, spatial resolution and gating of MRI data, but also field strength or method used for eddy current correction.…”
Section: Discussionsupporting
confidence: 80%
“…As previously reported (Table 4), we found that flow volume [1416, 21, 25, 26] and peak flow [14] were lower and that peak velocities were higher [18] when estimated using 4D flow in comparison with 2D measurements. Of note, our net volume measurements were lower than those previously reported both at 3T (2D-1dir = 89 ± 10 ml [18] or 100.6 ± 27.8 ml [16] and 4D flow = 88 ± 10 ml [18] or 95.9 ± 19.1 ml [16] in the AA). This could be due to the differences in the studied populations, spatial resolution and gating of MRI data, but also field strength or method used for eddy current correction.…”
Section: Discussionsupporting
confidence: 80%
“…However, until the recent implementation of under-sampling methods, including parallel imaging, the clinical utility of 4D flow MRI had been largely limited by prohibitively long image acquisition times (12). To date, although flow and function assessment have been described with 4D flow imaging (9, 1315), assessment of ventricular mass quantification has not yet been reported to our knowledge. Left ventricular (LV) mass quantification is commonly performed in the setting of congenitally corrected transposition of the great arteries after pulmonary arterial banding to assess feasibility of an arterial switch operation (16).…”
Section: Introductionmentioning
confidence: 99%
“…These errors, which manifest as phase shifts on a regional, global, and temporal basis, will compromise the ability to accurately quantify integrated parameters such as stroke volume 231-234 . A number of studies have investigated various correction approaches 57,234-236 ; however, there is no widespread agreement as to a universal correction protocol. The lack of standardised analysis tools for regional flow quantification and analysis of PC data with three-directional velocity encoding and/or 3D volumetric coverage is currently a major hurdle for their more widespread clinical application.…”
Section: Discussionmentioning
confidence: 99%